Different Spin‐State Behaviors in Isostructural Solvates of a Molecular Iron(II) Complex. Issue 5 (22nd December 2015) - Cook, Laurence J. Kershaw; Kulmaczewski, Rafal; Cespedes, Oscar; Halcrow, Malcolm A.
Abstract: The complex [FeL2 ][BF4 ]2 (1 ; L=4‐(isopropylsulfanyl)‐2, 6‐di(pyrazol‐1‐yl)pyridine) forms solvate crystals1 ⋅solv (solv=MeNO2, MeCN, EtCN, or Me2 CO). Most of these materials lose their solvent sluggishly on heating. However, heating1 ⋅MeNO2 at 450 K, or storing1 ⋅EtCN under ambient conditions, leads to single‐crystal to single‐crystal exchange of the organic solvent for atmospheric moisture, forming1 ⋅H2 O. Solvent‐free1 (1 ⋅sf) can be generated in situ by annealing1 ⋅H2 O at 370 K in the diffractometer or magnetometer. The different forms of1 are isostructural ( P 21 / c, Z =4) and most of them exhibit spin‐crossover (SCO) at 141≤ T 1 / 2 ≤212 K, depending on their solvent content. The exception is the EtCN solvate, whose pristine crystals remain high‐spin between 3–300 K. The cooperativity of the spin‐transitions depends on the solvent, ranging from gradual and incomplete when solv=acetone to abrupt with 17 K hysteresis when solv=MeCN. Our previously proposed relationship between molecular structure and SCO explains some of these observations, but there is no single structural feature that correlates with SCO in all the1 ⋅solv materials. However, changes to the unit cell dimensions during SCO differ significantly between the solvates, and correlate with the SCO cooperativity. In particular, the percentage change in unit cell volume during SCO for the most cooperative material, 1 ⋅MeCN, is 10 times smaller than for the other1 ⋅solv crystals. Abstract : Five solvate compounds [FeL2 ][BF4 ]2 ⋅solv (L=4‐[isopropylsulfanyl]‐2, 6‐di[pyrazol‐1‐yl]pyridine), plus the solvent‐free compound, are isostructural but exhibit quite different spin‐state behaviors. Small changes to the structure of the [FeL2 ] 2+ cation explain some of these observations. However, changes in the unit cell parameters during spin‐crossover correlate consistently with the spin‐transition cooperativity in all the materials.